Análisis Financiero a la Cooperativa de Ahorro y Crédito Inticoop Ltda. del Cantón Saraguro, período 2021-2022 - Puglla Maurad, Josselyn Anahi (2024)
The financial analysis developed in the Cooperativa de Ahorro y Crédito Inticoop Ltda. del Cantón Saraguro, period 2021 - 2022 allowed usto know the economic and financial situation using different methods and techniques. By means of the vertical analysis developed in the year 2022, the financial structure represented by the Assets in 100% and its largest item is the loan portfolio; the Liabilities with 81.10% and constituted largely by obligations with the public; the Equity represents 18.90% and is made up of the capital stock, reserves and results. The horizontal analysis reflects in the period 2021 - 2022 an increase of 8.01% in income and its interest and discounts earned with a variation of 6.79%; expenses have an increase of 8.40% with the largest variation being operating expenses with 29.79% and provisions with a decrease of 30.98% in 2022. Subsequently, the financial indicators of the Superintendency of Popular and Solidarity Economy were applied, determining a delinquency rate of 8% and 10% in the study periods due to the increase in the unproductive portfolio and the gross portfolio; the intermediation margin in relation to assets represents 20% for the first year and 16% for the second year due to the decrease in provisions and the increase in operating expenses; Liquidity presents 11% for 2021 and 10% for 2022 due to the increase in available funds and short-term deposits; the unproductive portfolio presents 35% for the first period and 37% for the second period, showing that the unproductive portfolio is growing year by year, thus affecting the entity's equity; finally, Solvency was developed under the use of the pearl monitoring system and registers 106% for 2021 and 103% for 2022, showing an increase in its assets and provisions as well as in its problematic assets. Finally, the technical report was prepared, allowing us to clearly recognize the areas in difficulty such as delinquency, liquidity, unproductive portfolio and solvency of the cooperative, thus facilitating the presentation of possible recommendations for improvement aimed at managers for better decision making.